2020
DOI: 10.3389/fonc.2020.00946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NOSES and Conventional Laparoscopic Surgery in Colorectal Cancer: Bacteriological and Oncological Concerns

Abstract: Background: Colorectal natural orifice specimen extraction surgery (NOSES) is considered to be a scarless operation that avoids the laparotomy of extraction specimen, but bacteriological and oncological concerns are raised with this technique. Objective: The purpose of this study was to compare the oncological and bacteriological outcomes of NOSES and conventional laparoscopic (CL) procedures. Methods: This is a retrospective study of prospectively collected outcomes data. Patients operated with colorectal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…The present study confirmed that La-NOSES and CLA were similar to Ouyan’s study ( 19 ) in terms of elevated postoperative inflammatory indicators, with a corresponding increase in postoperative CRP and PCT, and the present study further indicated that both indicators were significantly elevated at POD2 and gradually recovered at POD7. Among them, La-NOSES caused a more significant and statistically significant increase in CRP and PCT.…”
Section: Discussionsupporting
confidence: 91%
“…The present study confirmed that La-NOSES and CLA were similar to Ouyan’s study ( 19 ) in terms of elevated postoperative inflammatory indicators, with a corresponding increase in postoperative CRP and PCT, and the present study further indicated that both indicators were significantly elevated at POD2 and gradually recovered at POD7. Among them, La-NOSES caused a more significant and statistically significant increase in CRP and PCT.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, when choosing from these three methods, tumor location should be prioritized over complications [20]. To reduce the risk of infection after NOSES, the international consensus of NOSES recommends that preventive antibiotics should be used before surgery, defecation preparation should be improved, intra-abdominal irrigation should be performed during surgery, a large amount of povidone-iodine and saline should be used for anal cleaning, translucent wound protectors should be used, and pelvic or abdominal drains should be used [3] , [21]. These recommendations were followed in this study to reduce the possibility of bacterial contamination and abdominal infections.…”
Section: Discussionmentioning
confidence: 99%
“…As a new star of minimally invasive technology, NOSES is gradually being recognized and accepted by many clinicians because of the potential benefits including reduction in postoperative pain and wound complications, less use of postoperative analgesia, faster recovery of intestinal function, shorter hospital stay, and better cosmetic and psychological effects described in colorectal surgery [16]. Some researchers have proposed that, compared with the conventional laparoscopic procedure, NOSES is in conformity with the principle of asepsis and tumor-free technique and can be worthy of clinical application [17]. A systematic review and meta-analysis of NOSES showed that NOSES is a safe and viable alternative to traditional laparoscopy in colorectal oncology in terms of short-term results [18].…”
Section: Discussionmentioning
confidence: 99%